2015
DOI: 10.11646/zootaxa.3937.3.6
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong><em>Oscheius onirici</em> sp. n. (Nematoda: Rhabditidae): a new entomopathogenic </strong><br /><strong>nematode from an Italian cave</strong></p>

Abstract: Oscheius onirici sp. n. (Nematoda: Rhabditidae) was isolated from a karst cave soil of Central Italy. Molecular and morphological analyses were performed. Total DNA was extracted from individual nematodes and the mitochondrial COI, the ITS containing region, the D2-D3 expansion domains of the 28S rRNA gene and the 18S rRNA gene were amplified and sequenced. BLAST search at NCBI by using all molecular markers revealed that this taxon is similar to Oscheius species. Phylogenetic trees of ITS, 28S and 18S rDNA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…For this reason, several projects were conducted for the eradication of invasive alien species in Europe, as they are recognized to cause heavy impacts on native biodiversity Shine et al, 2009) and for the protection of native species and habitats in the Archipelago (http://www.montecristo2010.it, http:// www.restoconlife.eu/). Nematodes with other organisms present in the soil can be accidentally introduced via a range of human-associated pathways (Meagher, 1977;Hulme et al, 2008;Hughes et al, 2010), in particular as contaminant of traded plant propagation material (Davidson et al, 2005; McNeill et al, 2006) and through clothing and footwear (Baker, 1966;Davidson et al, 2005;Webber and Rose, 2008).Unfortunately, there is still a considerable lack of knowledge about the incidence and distribution of terrestrial nematodes (new species are continuously described, such as Oscheius onirici Torrini et al, 2015) and their status as alien or endemic. The only data concerning some heavy and famous pests of agriculture (e.g., Globodera spp.)…”
mentioning
confidence: 99%
“…For this reason, several projects were conducted for the eradication of invasive alien species in Europe, as they are recognized to cause heavy impacts on native biodiversity Shine et al, 2009) and for the protection of native species and habitats in the Archipelago (http://www.montecristo2010.it, http:// www.restoconlife.eu/). Nematodes with other organisms present in the soil can be accidentally introduced via a range of human-associated pathways (Meagher, 1977;Hulme et al, 2008;Hughes et al, 2010), in particular as contaminant of traded plant propagation material (Davidson et al, 2005; McNeill et al, 2006) and through clothing and footwear (Baker, 1966;Davidson et al, 2005;Webber and Rose, 2008).Unfortunately, there is still a considerable lack of knowledge about the incidence and distribution of terrestrial nematodes (new species are continuously described, such as Oscheius onirici Torrini et al, 2015) and their status as alien or endemic. The only data concerning some heavy and famous pests of agriculture (e.g., Globodera spp.)…”
mentioning
confidence: 99%
“…The presently studied population of this species was in association with galleries on bark samples of Pinus eldarica trees in the Lavizan region, Tehran. No morphological or morphometric differences were observed between the presently studied population and the original data given by Torrini et al (2015) (Fig. 4, Table 1).…”
Section: Oscheius Necromenus (Sudhaus and Schulte 1989)mentioning
confidence: 51%
“…Sudhaus (2011) with cadavers of the bombardier beetle (Smart and Nguyen 1994). Torrini et al (2015) reported and described the first entomopathogenic nematodes (EPN) belonging to the Dolichura group. This finding was further studied/ criticized by Campos-Herrera et al (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several EPN species, all symbiotic with bacterial strains of Serratia, have been found in the Heterorhabditidoides group (Heterorhabditidoides (=Oscheius) chongmingensis and H. rugaoensis) and the insectivora group (Oscheius carolinensis) (Zhang et al, 2008;Ye et al, 2010;Liu et al, 2012). Other Oscheius species are parasitic to insects, some of them also commonly associated with Serratia (Lephoto et al, 2015;Torrini et al, 2015), although their entomopathogenicity has yet to be examined according to the criteria of EPNs revised by Dillman et al (2012).…”
mentioning
confidence: 99%